VIRTUAL LABORATORY OF ELECTRICITY CONCEPT TO IMPROVE PROSPECTIVE PHYSICS TEACHERS CREATIVITY - Gunawan, G.; Harjono, A.; Sahidu, H.; Herayanti, L. (Jurnal Pendidikan Fisika Indonesia, 2017)
A virtual laboratory for electrical materials has been developed in this study. The virtual laboratory was developed as an alternative laboratory due to the limited equipment of physics experiments and simultaneously assisting students in visualizing abstract concepts in physics. This article discusses the results of testing on the effects of virtual laboratories on improving the creativity of prospective physics teachers. Measurable creativity includes verbal and figural creativity. The model testing process uses the quasi-experimental method. The participant of this research is prospective physics teachers in Faculty of Teacher Training and Education, University of Mataram. The research instrument used in the form of tests of verbal and figural creativity related to the electrical material being studied. The results showed that there is a difference in the improvement of prospective physics teachers’ creativity after learning in both groups. In general, the increase in creativity in the experimental group is higher than the control group. The increase in verbal and figural creativity of the two groups also differed significantly. In both groups, the increase of verbal creativity is higher than that of figural creativity. This suggested that the developed virtual lab model proved to enhance the creativity of prospective physics teachers.